Development of Interactive IPAS Teaching Material Based on the Inquiry Model Using the Powtoon Application for Fourth Grade Elementary School Students - Maimon Hidayat; Ulfia Rahmi; Jasrial; Zuwirna (Jurnal Penelitian Pendidikan IPA, 2025)
This study aims to develop interactive teaching materials based on the inquiry model using the Powtoon application that are valid, practical, and effective for fourth-grade elementary school students. The background of this research includes the limited use of technology-based teaching materials, low student participation in science and social science learning, a lack of engaging instructional media, and the need for learning models that enhance critical thinking and problem-solving skills. The method used is Research and Development (R&D) with the 4D development model (Define, Design, Develop, and Disseminate). The validation results from subject matter experts, media experts, and language experts indicate that the developed teaching materials are highly valid, with a score of 90.04%. The materials include content aligned with the Competency Criteria and Learning Objectives, a systematic presentation following the inquiry model syntax, communicative language, and attractive visuals through Powtoon animations. In terms of practicality, both students and teachers rated the material as highly practical, with an average student response score of 86.98% and a teacher score of 92.67%. The effectiveness of the teaching material was evaluated through pretest and posttest, with an average N-Gain score of 0.79 (high category), showing a positive impact on student learning outcomes. These materials are proven to be valid, practical, and effective in improving student learning outcomes.